014 Time Course of Changes in Erectile Function in Men with Functional Hypogonadism Receiving Long-Term Testosterone Therapy in Comparison to an Untreated Control Group. (1st May 2022) - Saad, F.; Haider, A.; Haider, K.S.; Doros, G.; Traish, A.
ABSTRACT: Introduction: There still seem to be controversies regarding the effectiveness of testosterone therapy (TTh) on erectile function. There is limited information as to the duration of treatment required to achieve maximum effect. Hackett et al. have suggested that erectile function improves up to 3.8 years in men with hypogonadism and diabetes receiving continuous long-term TTh (World J Mens Health 2020;38):68-77). Objective: To study erectile function in men with functional hypogonadism (after excluding 86 patients with primary hypogonadism) in a registry study and assessing year-to-year changes. Methods: In a hypogonadism registry from a single urology center, 779 men had functional hypogonadism. 386 opted for TTh (T-group) and received 3-monthly injections of testosterone undecanoate following an initial 6-week interval, 393 against TTh (CTRL). Changes over time between groups were compared and adjusted for age, weight, waist circumference, fasting glucose, blood pressure, lipids, and quality of life to account for baseline differences between the two groups. Results: Mean age: T-group: 58.4±6.4, CTRL: 63.1±4.8 years (p<0.0001), mean (median) follow-up 8.9±2.6 (10) and 9.6±2.3 (11) years. Baseline IIEF-EF was 17.3±5.8 in the T-group and 19.8±3.4 in CTRL. Use of PDE5 inhibitors at baseline was 25.8% in the T-group and 22.1% in CTRL (p=0.2181). The following data are shown as least squares means: IIEF-EF: T-group: IIEF-EF increased at the end of each consecutive year vs. baseline by 2.2 (year 1), 4.7 (year 2), 5.6 (year 3), 6.4 (year 4), 6.9 (year 5), 7.4 (year 6), 7.8 (year 7), 8.3 (year 8), 8.8 (year 9), 9.1 (year 10), and 9.8 (year 11). The change was statistically significant vs. previous year for the first 6 years with a p-value of p<0.0001, from year 7 to year 6 with a p-value of p=0.0043, from year 8 to year 7 with a p-value of p=0.0002, from year 9 to year 8 with a p-value of p<0.0001, from year 10 to year 9 with a p-value of p=0.0417, and from year 11 to year 10 with a p-value of p<0.0001. CTRL: IIEF-EF decreased at the end of each consecutive year vs. baseline by 1.7 (year 1), 3.6 (year 2), 5.1 (year 3), 6.3 (year 4), 7.5 (year 5), 8.7 (year 6), 9.8 (year 7), 10.7 (year 8), 11.5 (year 9), 12.2 (year 10), and 12.7 (year 11). The change was statistically significant vs. previous year for the all 11 years with a p-value of p<0.0001. The estimated adjusted difference between groups at 11 years was 22.5 (95% CI: 21.9;23.2) (p<0.0001). Medication adherence in the T-group was 100 per cent as all injections were performed in the office and documented. Conclusions: Long-term TTh in men with functional hypogonadism continuously improved erectile function during 11 years of observation. In an untreated control group, erectile function continuously deteriorated. Disclosure: Work supported by industry: yes, by Bayer AG. A consultant, employee (part time or full time) or shareholder is among the authors (Bayer AG).